2016
DOI: 10.1038/srep31853
|View full text |Cite
|
Sign up to set email alerts
|

Space radiation exposure persistently increased leptin and IGF1 in serum and activated leptin-IGF1 signaling axis in mouse intestine

Abstract: Travel into outer space is fraught with risk of exposure to energetic heavy ion radiation such as 56Fe ions, which due to its high linear energy transfer (high-LET) characteristics deposits higher energy per unit volume of tissue traversed and thus more damaging to cells relative to low-LET radiation such as γ rays. However, estimates of human health risk from energetic heavy ion exposure are hampered due to lack of tissue specific in vivo molecular data. We investigated long-term effects of 56Fe radiation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 83 publications
1
15
0
Order By: Relevance
“…At molecular level, long-term changes in DNA methylation patterns ( 149 ), distinctive miRNA signatures ( 150 ) were described in the brain following proton irradiation. Similar to γ-rays, heavy ion exposure also increased circulating leptin levels ( 151 ). It was reported by Baluchamy et al that high-energy protons induced a dose-dependent increase in reactive oxygen species and lipid peroxidation as well as a reduction in antioxidant levels in the brain, mainly in the neural stem cells, followed by apoptotic cell death ( 152 155 ).…”
Section: Low-dose Radiation Effects On the Brainmentioning
confidence: 99%
“…At molecular level, long-term changes in DNA methylation patterns ( 149 ), distinctive miRNA signatures ( 150 ) were described in the brain following proton irradiation. Similar to γ-rays, heavy ion exposure also increased circulating leptin levels ( 151 ). It was reported by Baluchamy et al that high-energy protons induced a dose-dependent increase in reactive oxygen species and lipid peroxidation as well as a reduction in antioxidant levels in the brain, mainly in the neural stem cells, followed by apoptotic cell death ( 152 155 ).…”
Section: Low-dose Radiation Effects On the Brainmentioning
confidence: 99%
“…Pulmonary radiationinduced gross metabolic abnormalities may be age-, physical status-, and dose-sensitive because populations with lung tumors are older, disease status, and use of fractionated dose regimes [$8 Gy]. female C57BL/6J mice that received a whole-body single exposure of 1.6 Gy 56Fe radiation (energy: 1000 MeV/n; LET: 148 keV/lm), which is equitoxic to 2 Gy of gamma radiation (Suman et al 2016), became overweight; Babbitt et al also found that young (weanling, 3 weeks) female C57BL/6 mice irradiated with four equal weekly cobalt-60 exposures (total cumulative doses: 3-5.1 Gy) (Babbitt et al 2001) had increased body weight. However, we found that female C57BL/6 mice exposed to 5 Gy TBI or 9 Gy sub-TBI did not become overweight, whereas mice exposed to 12.5 TRI did experience a significant increase in body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from carcinogenesis, radiation exposure has been related to obesity in humans (Sklar et al 2000;Oeffinger et al 2003;Ross et al 2004;Razzouk et al 2007) and animals (Babbitt et al 2001). Suman et al observed increased obesity-related factors 12 months after 56-Fe radiation exposure in female C57BL/6J mice (Suman et al 2016). Studies have shown genetic-related (Carter et al 1997;Fearnside et al 2008) and sex-related (Hwang et al 2010;Yang et al 2014) differences in dietinduced body weight increases in various mouse strains.…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse studies, these bacterial challenges are non-toxic to normal mice. But under the conditions of heavy ions radiation, mice were morbidity or mortality [17][18][19]. Therefore, morbidity or mortality could be prevented by relieving I immune tissues injury.…”
Section: Discussionmentioning
confidence: 99%